Dietary Intake of Macro and Micro-Minerals among Participants with Alexithymia in Jordan: A Cross-Sectional Study - Ibrahim, Mohammed O. (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: Alexithymia is a condition characterized by inability in explaining and describing feelings, distinguishing bodily sensations, and expressing feelings toward others. The relationships between alexithymia and dietary intakes of minerals among Jordanian people have not been well-characterized. Therefore, the aim of the study was to investigate the associations between dietary intakes of macro- and micro-minerals and alexithymia. Methods: Seven hundred and fifty three Jordanian adults completed face-to-face interviews through cross-sectional study conducted among voluntary participants aged 18-64 years. Every participant was asked to fill in questionnaires regarding their socio-demographic characteristics, anthropometric measurements, and dietary intakes. The 20-item Toronto Alexithymia Scale (TAS-20) was used for measuring alexithymia among participants. Data analysis was conducted using SPSS (version 25). Statistical significance was set at p-value <0.05. Results: Findings of the study indicated that about 10.4% of Jordanian adults classified with having alexithymia with scores of (TAS-20) Scale ≥ 61. Females, participants with monthly incomes higher than 700 JOD, participants with low educational levels, and obese participants scored significantly higher scores of (TAS-20) scale in comparison to other groups for each variable. Odds ratios for associations between alexithymia quartiles of dietary intake of minerals were calculated after adjusting for gender, education level, physical activity, and BMI. By comparing highest intake (Quartile 4) with the lowest intake (Quartile 1), adjusted odds ratios have shown that two macro-minerals (calcium and magnesium) and three micro-minerals (iron, zinc, and selenium) have significant negative association with alexithymia. Conclusion: The distribution of alexithymia among Jordanian adults was very low. Mental conditions require appropriate dietary interventions that assure the maintaining of healthy weight and the consumption of adequate intakes of nutrients especially macro- and micro-minerals. Further observational and experimental studies are highly recommended to explore the role of action and specific mechanisms of these minerals with mental conditions such as alexithymia.